A review of international trade impacts on sustainable development - Ningkang Chen; Zounachuan Sun; Zhenci Xu; Junying Xu (Marine Development)
Abstract As globalization accelerates, the expansion of international trade has profound implications for sustainable development, influencing economic growth, social equity, and environmental sustainability. While existing research has extensively explored the effects of trade on specific Sustainable Development Goals (SDGs), there is a lack of comprehensive analysis that captures its complex and interconnected impacts. This paper employs the Metacoupling framework to systematically examine how international trade affects sustainable development across multiple dimensions. By analyzing the roles of internal, adjacent, and distant trade interactions, we reveal significant disparities in neighboring and distant influences of trade across different regions. Our findings offer a novel perspective by illustrating how the cross-scale dynamics of international trade create both direct and indirect feedback that amplify or mitigate sustainable development outcomes. Specifically, we uncover the hidden pathways through which trade indirectly shapes resource distribution, environmental pressures, and socio-economic inequalities, challenging conventional theories about trade-development relationships. These findings underscore the need for integrated policy approaches that address the trade-offs between economic, social, and environmental goals. By offering a holistic perspective on the dynamic relationship between international trade and SDGs, we provide valuable insights for shaping more sustainable global trade practices.